The status of the girl child under international law : a semioethic analysis / Clara Chapdelaine-Feliciati. - Chapdelaine-Feliciati, Clara, 1981- (Cambridge University Press, 2025)
Clara Chapdelaine-Feliciati offers the first comprehensive study of the status of the girl child under international law. This book significantly contributes to bridging two fields usually studied separately: law and semiotics. The author engages in the novel legal semiotics theory to decode the meaning of international treaties (mainly the Convention on the Rights of the Child, Convention on the Elimination of All Forms of Discrimination Against Women, and International Covenants) and assess whether the provisions, as formulated, clearly identify the girl child and take into account the obstacles she faces as a result of sexism, childism, and intersectional discrimination. This is also the first book to apply The Significs Meaning Triad - Sense, Meaning, Significance - in international law, and Semioethics for both a diagnosis and prognosis of problematic signs in view of modifying the wording of relevant treaties.